Forgiveness in post-apartheid South Africa - Lotter, George A (Acta Theologica, 1996)
In this article the issue of forgiveness is addressed as it should be dealt with on a macro, meso and micro in South African society. Biblical guidelines and the necessity for forgiveness in the situation in post-apartheid South Africa are looked into. Pointers in the process of forgiveness are proposed bringing forward the importance of the church, scholars and the individual Christian. The author concludes that there is a real need for thoroughgoing study of and application to this crucial matter in post-apartheid South Africa but in the end forgiveness can only be attained as a "transcendent gift" from God.